TRADISI PERNIKAHAN MENGELILINGI PUNDEN, SUMUR DAN MANDI AIR SENDANG MENURUT PANDANGAN ‘URF - Iswiyah, Deviyana Khoirotul; Sabiq, Fairuz (Hukum Islam, 2023)
This research discusses wedding traditions which have various versions of the procession according to the culture and context in which the wedding is held. Among the wedding processions that are considered unique, one of them is the wedding tradition of surrounding punden, wells and spring water bathing in Gembong Hamlet, Malanggaten Village, Kebakkramat District, Karanganyar Regency, Central Java. This tradition is interesting to study because every bride and groom who comes from that area or if only one of the bride and groom is a native of that area, both of them still have to carry out this tradition. The type of research in this study is field research and to achieve this goal the author uses a descriptive qualitative approach. Data collection was achieved through observation, interviews and documentation studies. Interviews were conducted with several residents of Gembong Hamlet, Malanggaten Village, Kebakkramat District, Karanganyar Regency. The results of this research show that the wedding tradition of surrounding punden, wells and bathing in spring water is a traditional wedding tradition in Gembong Hamlet, Malanggaten Village, Kebakkramat District, Karanganyar Regency, the implementation of which refers to the culture of the Surakarta palace. In terms of its validity, this tradition is categorized as 'Urf ṣahih, because it is known to the public and does not conflict with the Islamic propositions', so the implementation of this wedding tradition is permissible. This tradition is permitted because the essence of its implementation is to offer prayers to Allah SWT, and aims to introduce local residents to the ancestors who built the village, preserve the culture that has been passed down from generation to generation, and maintain local wisdom.